Inhibition of Postn Rescues Myogenesis Defects in Myotonic Dystrophy Type 1 Myoblast Model - Shen, Xiaopeng; Liu, Zhongxian; Wang, Chunguang; Xu, Feng; Zhang, Jingyi; Li, Meng; Lei, Yang; Wang, Ao; Bi, Chao; Zhu, Guoping (Frontiers in Cell and Developmental Biology, 2021)
Myotonic dystrophy type 1 (DM1) is an inherited neuromuscular disease caused by expanded CTG repeats in the 3′ untranslated region of the DMPK gene. The myogenesis process is defective in DM1, which is closely associated with progressive muscle weakness and wasting. Despite many proposed explanations for the myogenesis defects in DM1, the underlying mechanism and the involvement of the extracellular microenvironment remained unknown. Here, we constructed a DM1 myoblast cell model and reproduced the myogenesis defects. By RNA sequencing, we discovered that periostin (Postn) was the most significantly upregulated gene in DM1 myogenesis compared with normal controls. This difference in Postn was confirmed by real-time quantitative PCR and western blotting. Moreover, Postn was found to be significantly upregulated in skeletal muscle and myoblasts of DM1 patients. Next, we knocked down Postn using a short hairpin RNA in DM1 myoblast cells and found that the myogenesis defects in the DM1 group were successfully rescued, as evidenced by increases in the myotube area, the fusion index, and the expression of myogenesis regulatory genes. Similarly, Postn knockdown in normal myoblast cells enhanced myogenesis. As POSTN is a secreted protein, we treated the DM1 myoblast cells with a POSTN-neutralizing antibody and found that DM1 myogenesis defects were successfully rescued by POSTN neutralization. We also tested the myogenic ability of myoblasts in the skeletal muscle injury mouse model and found that Postn knockdown improved the myogenic ability of DM1 myoblasts. The activity of the TGF-/Smad3 pathway was upregulated during DM1 myogenesis but repressed when inhibiting Postn with a Postn shRNA or a POSTN-neutralizing antibody, which suggested that the TGF-/Smad3 pathway might mediate the function of Postn in DM1 myogenesis. These results suggest that Postn is a potential therapeutical target for the treatment of myogenesis defects in DM1.